Learning Style Practices and Learners’ Proficiency Level in Music, Arts, Physical Education, and Health (American Journal of Arts and Human Science, 2025)
Learning styles refer to how learners absorb and understand concepts in their subjects. However, many students struggle with grasping the concepts and terminologies in MAPEH. This study aimed to assess the extent of learning style practices and proficiency levels in MAPEH among Grade 5 learners in the Central and North I districts of Cagayan de Oro City during the School Year 2023-2024. Specifically, it examined the respondents’ learning style practices, their proficiency levels in MAPEH for the First and Second Quarters, and the relationship between these variables. Data were collected from 332 respondents using a modified questionnaire based on Grasha and Reichmann’s Learning Style model. The study employed a descriptive research design and utilized frequency, mean, standard deviation, and Pearson Product Moment Correlation for data analysis. Results indicated that collaborative learning was the most practiced style, and students achieved a high proficiency in MAPEH. A significant relationship was found between learning style practices and proficiency levels. It is recommended that teachers implement diverse, interactive, and differentiated activities to minimize avoidant learning styles. Additionally, struggling learners should participate in tailored interventions, ensuring teachers and students work together to maximize learning potential and achieve the highest proficiency levels.